MODELING OF NATURAL TURBULENT CONVECTION IN AN ENCLOSURE WITH LOCALIZED HEATING - Kiprop, Josephat Kiplagat; Otieno, Dr. Awuor Kennedy (Journal of Statistics and Actuarial Research, 2019)
Purpose: The purpose of the study was to model natural turbulent convection in an enclosure with localized heating. Methodology: The study considered the equations governing a free convection. Precisely, the equations governed a Newtonian fluid that experiences transfer of heat or mass. The governing equations were derived from the conservation principles namely the conservation of mass, the conservation of momentum, and the conservation of energy. These equations were decomposed using the Reynolds decomposition then the decomposed equations were non-dimensionalized and reduced using the Boussinesq assumptions. The k-Îµ model was employed in the simulation of flow characteristics. Finally, the equations were solved numerically for the flow quantities. Results: The results were presented in form of isotherms and vector potentials in different sections of the enclosure. The results of the study indicated that the variation of the Rayleigh number affects the flow properties such as the velocity and temperature. Specifically, it was found that the increase in the Rayleigh number results in the increase in the velocity magnitude and a decrease in temperature. Unique contribution to theory, practice and policy: The determination of flow properties is attained with the change in the dimensions of the enclosure and keeping the aspect ratio constant. Furthermore, the bottom wall is heated while the top wall is cold and the other four walls are adiabatic. It is recommended that and investigation is carried out instances where: one makes use of a difference turbulence model such as the k-Ï‰ SST turbulence model and observe the fluid properties one carries out an investigation keeping the Rayleigh number constant and varying the aspect ratio and the dimensions of the enclosure and where investigation of the fluid properties in the enclosure with a heater being introduced at the bottom wall and a window at the top wall.